PENGARUH DAR, ROA, CR TERHADAP HARGA SAHAM DI PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI PERIODE 2015-2019 - Jordan Kristian Bonar Pane; Meliyani Meliyani; Diana Theresia Br Pandia; Stephen Windu Sihombing; Mila Yulia Herosian (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2021)
This study analyzes the effect of Debt to Asset Ratio, Return On Assets, Current Ratio on Stock Prices in Consumer Goods Industrial Sector Companies listed on the IDX. The sample used in this study were 25 manufacturing sub-sector companies on the Indonesia Stock Exchange for the 2015-2019 period using the documentation method. existing data are published and listed on the IDX. Approach This research uses quantitative research and this type of research uses descriptive statistical research. The results showed that the Debt to Asset Ratio had an effect on stock prices, Return On Assets had no effect on stock prices and the Current Ratio had an effect on stock prices. Simultaneously Debt to Asset Ratio, Return On Assets, Current Ratio have an influence on the dependent variable, namely stock prices.Keywords:            Debt To Asset Ratio (DAR); Return on Assets (ROA); Current Ratio (CR); Stock price.